Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J.a; García, C; Hernández, T; Moreno, J L; Ros, M (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation

Low molecular weight phenols in cork stoppers - Pena-Neira, A; Hernández, T; GARCIA-VALLEJO, M C; Cadahía, E; de Simon, B F; Suarez, J A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1999)
In this work, we study the low molecular-weight polyphenols in cork stoppers obtained from commercial wine bottles and in samples taken at five stages of the cork stopper manufacturing process. The phenolic compounds (acids, aldehydes, and coumarins) were analyzed by high pressure liquid chromatography with photodiode array detector. The results were studied by statistical methods in order to determine the relationship among these compounds and their variability throughout the industrial processing. Discriminant analysis showed that the phenolic composition allows differentiation of each stage in the manufacture of cork stoppers and the different provenances of stoppers obtained from commercial wine bottles. The results showed wide variations in phenolic content among cork stoppers within each region and each winery.
Keywords: Cork; phenolic compounds; stopper manufacturing

Low molecular-weight phenolic compounds in natural and agglomerated cork stoppers - Pena-Neira, A; BartolomÉ, B; Cadahía, E; Hernández, T; Garcia-Vallejo, C; GONZALEZ-ADRADOS, J R; Suarez-Lepe, J A (SCIENCES DES ALIMENTS, 1999)
The low molecular-weight phenolic compounds in cork stoppers used for the closure of wine bottles are studied. Different phenolic acids (gallic, protocatechuic, vanillic, caffeic, ferulic and ellagic), aldehydes (protocatechuic, p-hydroxybenzoic, vanillin, ethylvanillin and coniferilic), and coumarins (aesculetin and scopoletin) were determined in natural cork stoppers (untreated and chlorine-bleached) and in agglomerated cork stoppers (unbleached and peroxide-bleached). The ketone 2,3-dihydroxy-1-guaiacylpropan-1-one and four ellagic-acid-type tannins were detected in natural stoppers. The amount of most of the phenolic compounds studied was higher in the natural cork stoppers than in agglomerated stoppers. In natural cork stoppers, an Increase in the content of caffeic and ferulic acids and vanillin was observed after chlorine bleaching. In agglomerated stoppers however, peroxide bleaching produced a decrease in the content of these same compounds.
Keywords: Cork; low molecular-weight phenolic; Stopper; stopper treatment

Biological and biochemical indicators in derelict soils subject to erosion - García, C; Hernández, T (Soil Biology and Biochemistry, 1997)
n 21 derelict soils from a semi-arid Spanish Mediterranean area, with a lithological sub- strate of Ioams, submitted to a high degree of erosion, several biological and biochemical properties in- dicative of the soil degradation leve1 were determined. The organic matter content of these soils was very low (mean value = 11.8 g kg-‘), approximately one-third of the average value for organic matter content of natura1 soils in the same zone. Biological properties such as basal respiration and biomass C also had low values and were positively correlated with the organic matter content. Low values for de- hydrogenajse and catalase activity were indicative of low biological activity of the degraded soils. A positive correlation was found between the hydrolases related with the N, P, C and S cycles (urease, proteases, fl-glucosidase and arylsulphatase), as wel1 as between these hydrolases and the organic matter content. Principal component analysis showed that ah the variables studied, except catalase and qCOr, had a similar behaviour. There was a negative correlation between many of the properties studied and electrical conductivity, which agreed with the higher degree of biological and biochemical degradation found in gypsiferous soils with a higher salt content. Arylsulphatase and p-glucosidase activity were the hydrolases most affected by soil erosion processes
Keywords: biochemical parameters (PG); Biological indicators; derelict soils; Soil degradation